Preparation method of high-quality Ti60 titanium alloy bar and product

Through the process of multiple vacuum self-consumption smelting and upsetting forging, the problem of insufficient composition and structure uniformity of Ti60 titanium alloy rods in the prior art is solved, and the production of large-scale titanium alloy rods with low impurities and high uniformity is achieved, which is suitable for industrial production.

CN119592827APending Publication Date: 2025-03-11HUNAN GOLDSKY TITANIUM IND TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411789644.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The prior art is difficult to produce Ti60 titanium alloy rods with low impurities (Fe≤0.008%, O≤0.075%) and high composition uniformity, especially in large specifications and industrial production.

Method used

The comprehensive process of multiple vacuum self-consumption smelting and upsetting forging is adopted, including raw material selection, electrode pressing, electrode welding, vacuum self-consumption smelting and upsetting forging, etc., to ensure the composition uniformity and tissue uniformity of the ingot.

Benefits of technology

It has achieved the production of Ti60 titanium alloy rods with low impurities and high composition uniformity. It is suitable for large-sized rods of Φ300~500mm, meets the needs of industrial production, and improves the creep performance and thermal stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592827A_ABST
    Figure CN119592827A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-quality Ti60 titanium alloy bar and a product, a titanium alloy cast ingot with low impurities (Fe is less than or equal to 0.008% and O is less than or equal to 0.075%) and high component uniformity can be produced, the diameter of the produced cast ingot finished product is phi 580mm-phi 780mm, meanwhile, the cast ingot can be used for producing a large-specification bar with phi 300-500mm, and the preparation method is suitable for industrial production. The method comprises the following steps: (1) selecting raw materials; (2) electrode pressing; (3) electrode welding; (4) carrying out vacuum consumable smelting for the first time; (5) secondary vacuum consumable smelting; (6) carrying out third vacuum consumable smelting; (7) single-phase region fire-insulation reversing upsetting and drawing; (8) performing fire-insulation reversing upsetting and drawing on the two-phase region; and (9) two-phase region drawing-out forging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of titanium alloy manufacturing, and in particular to a method for preparing a high-quality Ti60 titanium alloy bar, and a product manufactured according to the method for preparing the high-quality Ti60 titanium alloy bar. Background Art

[0002] The main components of Ti60 titanium alloy are Ti-Al-Sn-Zr-Mo-Si-Ta-Nb-C, which is a 600℃ high-temperature titanium alloy. In the latest titanium alloy grade and chemical composition standard [GB / T 3620.1-2016], the components in Ti60 are consistent with the grade TA33. This alloy is often used to manufacture key parts such as integral blades, impellers and drums of aircraft engines. 600℃ is the biggest "thermal barrier" encountered in the development of traditional high-temperature titanium alloys. The main reason is that at such a high temperature, the creep resistance and thermal stability plasticity of titanium alloys drop sharply, affecting their use. Relevant studies have shown that the impurity element Fe has a large diffusion capacity in titanium alloys, which is 103 to 105 times the self-diffusion coefficient of Ti. Trace Fe elements will also significantly promote the self-diffusion of Ti, increase the dislocation climb rate, and thus reduce the creep performance. In order to improve the creep performance, the impurity Fe element content must be strictly controlled; at the same time, O element is an α-stabilizing element. Although it can significantly improve the tensile strength of titanium alloys, it significantly reduces the plasticity of titanium alloys. In order to improve thermal stability and plasticity, the impurity O element content must be strictly controlled. Since the types of Ti60 alloy components are significantly more than those of general titanium alloys, the properties of each element are quite different (the melting point is different, and the melting point of elements such as Al is significantly lower than that of other elements), the production process is relatively long, and it is affected by raw materials, atmospheric environment and process control. It is difficult to produce an ingot with low O, low Fe and high uniformity by engineering. At the same time, as the specifications of titanium alloy bars for aero-engines increase, the corresponding organizational uniformity improves and the level of ultrasonic flaw detection noise increases, the detectability of defects will be improved, which can reduce the occurrence of failures caused by undetected material defects. Therefore, it is extremely meaningful to invent a production method that can achieve the above purpose. Summary of the invention

[0003] In order to overcome the defects of the prior art, the technical problem to be solved by the present invention is to provide a method for preparing high-quality Ti60 titanium alloy rods, which can produce titanium alloy ingots with low impurities (Fe≤0.008%, O≤0.075%) and high composition uniformity. The diameter of the finished ingots produced is Φ580mm-Φ780mm. At the same time, the ingots can be used to produce large-size bars of Φ300~500mm, which are suitable for industrial production.

[0004] The technical solution of the present invention is: a method for preparing high-quality Ti60 titanium alloy bars, which comprises the following steps:

[0005] (1) Raw material selection: The raw materials are selected from titanium sponge with a particle size of 0.83-12.7 mm and a particle size of

[0006] 5.0~13.0mm aluminum beans, particle size ≤0.8mmAl-60Ta, particle size a×b×c Ti-80Sn, particle size 1.0~12.0mm sponge zirconium, particle size ≤0.8mmAl-60Mo, particle size

[0007] 0.25~4.0mmTi-50Si, particle size ≤1.5mmAl-60Nb, particle size 200 mesh C powder, the range of a is 3.0~15.0mm, the range of b is 3.0~5.0mm, and the range of c is 0.05~0.5mm;

[0008] (2) Electrode pressing: After mixing the above raw materials for 30-90 seconds, use an 8000-ton hydraulic press to press them into a density of 3.5-3.6 g / cm 3 The electrode block is pressed with titanium sponge as the base to reduce the powdered master alloy from spilling during the pressing process;

[0009] (3) Electrode welding: In a vacuum plasma welding box, a water-cooled copper electrode tip welding gun is used to perform argon-filled welding on the electrode block. The weld is evenly and symmetrically distributed on the circumference. The pre-vacuum is ≤0.08 mbar, the leakage rate is ≤0.008 mbar / min, and the argon flow rate is 10 to 27 L / min.

[0010] (4) The first vacuum consumable melting: The welded electrode is subjected to the first vacuum consumable melting, with the vacuum before melting ≤2Pa, the vacuum during melting ≤8Pa, the gas leakage rate ≤0.8Pa / min, the melting voltage 29-35V, the melting current 13-18kA, and the arc stabilization current 6.0-10.0A;

[0011] (5) Second vacuum consumable melting: The ingot that has completed the first vacuum consumable melting is subjected to the second vacuum consumable melting, with the vacuum before melting ≤1.3Pa, the vacuum during melting ≤5Pa, and the gas leakage rate ≤

[0012] 0.7Pa / min, melting voltage 30~39V, melting current 20~24kA, arc stabilization current

[0013] 10.0~15.0A / 6~10S;

[0014] (6) The third vacuum consumable melting: The ingot that has completed the second vacuum consumable melting is subjected to the third vacuum consumable melting, with the vacuum before melting ≤1.3Pa, the vacuum during melting ≤5Pa, and the leakage rate ≤

[0015] 0.7Pa / min, melting voltage 30~39V, melting current 23~28kA, arc stabilization current

[0016] 10.0~14.0A / 6~10S, during the feeding stage, fill with argon ≤5Pa, maintain vacuum 4-5Pa;

[0017] (7) Single-phase interval fire reversing upsetting and drawing: the ingot is heated at 1080-1200℃, and after being heated through, it is taken out of the furnace and forged for 1-2 fires of upsetting and drawing. Each fire has 2 upsettings and 2 drawing. The deformation mode of the last upsetting and drawing in the last fire of this stage is axial upsetting and side drawing, which changes the original axial direction of the forging billet. After forging, it is air-cooled or the hot material is returned to the furnace; the forging billet is heated through at 20-60℃ below the phase transformation point, and then 1 upsetting and 1 drawing are carried out. After forging, the hot material is returned to the furnace and heated through at 40-120℃ above the phase transformation point, and then 1 upsetting and 1 drawing are carried out. The deformation mode of the last upsetting and drawing in the last fire of this stage is side upsetting and axial drawing. After forging, the axial direction of the billet is equivalent to the axial direction of the original ingot;

[0018] (8) Two-phase separation fire reversing upsetting and drawing: After the forging billet is heated at 20-60℃ below the phase transformation point, it is subjected to one upsetting and one drawing. After forging, it is air-cooled or the hot material is returned to the furnace. The one upsetting and one drawing process is repeated 4-6 times. In this stage, the second upsetting and drawing deformation mode is axial upsetting and side drawing, which changes the original axial direction of the forging billet. The last upsetting and drawing deformation mode is side upsetting and axial drawing. After forging, the axial direction of the billet is equivalent to the axial direction of the original ingot.

[0019] (9) Two-phase zone drawing forging: The forging blank is heated at 20 to 60°C below the phase transformation point and then drawn forged. After forging, it is air-cooled or the hot material is returned to the furnace until it is drawn and rounded to the corresponding finished bar.

[0020] The present invention can produce titanium alloy ingots with low impurities (Fe≤0.008%, O≤0.075%) and high composition uniformity, and the diameter of the produced ingot product is Φ580mm-Φ780mm. At the same time, the ingot can be used to produce large-size bars with a diameter of Φ300-500mm, which is suitable for industrial production. The titanium alloy bar manufactured by the preparation method of the high-quality Ti60 titanium alloy bar is also provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Schematic diagram of the longitudinal chemical composition sampling positions of the ingot.

[0022] Figure 2 Schematic diagram of the transverse chemical composition sampling position at the ingot riser end.

[0023] Figure 3 The transverse and longitudinal microstructures of the rod of Example 1 are shown.

[0024] Figure 4 The transverse and longitudinal microstructures of the rod of Counterexample 1 are shown.

[0025] Figure 5 The figure is a flow chart of a method for preparing high-quality Ti60 titanium alloy rod according to the present invention. DETAILED DESCRIPTION

[0026] like Figure 5 As shown, a method for preparing high-quality Ti60 titanium alloy rods comprises the following steps:

[0027] (1) Raw material selection: The raw materials are selected from titanium sponge with a particle size of 0.83-12.7 mm and a particle size of

[0028] 5.0~13.0mm aluminum beans, particle size ≤0.8mmAl-60Ta, particle size a×b×c Ti-80Sn, particle size 1.0~12.0mm sponge zirconium, particle size ≤0.8mmAl-60Mo, particle size

[0029] 0.25~4.0mmTi-50Si, particle size ≤1.5mmAl-60Nb, particle size 200 mesh C powder, the range of a is 3.0~15.0mm, the range of b is 3.0~5.0mm, and the range of c is

[0030] 0.05~0.5mm;

[0031] (2) Electrode pressing: After mixing the above raw materials for 30-90 seconds, use an 8000-ton hydraulic press to press them into a density of 3.5-3.6 g / cm 3 The electrode block is pressed with titanium sponge as the base to reduce the powdered master alloy from spilling during the pressing process;

[0032] (3) Electrode welding: In a vacuum plasma welding box, use a water-cooled copper electrode head welding gun to perform argon welding on the electrode block. The welds are evenly and symmetrically distributed on the circumference. The pre-vacuum is ≤

[0033] 0.08mbar, leakage rate ≤0.008mbar / min, argon flow rate 10~27L / min;

[0034] (4) The first vacuum consumable melting: The welded electrode is subjected to the first vacuum consumable melting, with the vacuum before melting ≤2Pa, the vacuum during melting ≤8Pa, the gas leakage rate ≤0.8Pa / min, the melting voltage 29-35V, the melting current 13-18kA, and the arc stabilization current 6.0-10.0A;

[0035] (5) Second vacuum consumable melting: The ingot that has completed the first vacuum consumable melting is subjected to the second vacuum consumable melting. The vacuum before melting is ≤1.3Pa, the vacuum during melting is ≤5Pa, and the leakage rate is

[0036] ≤0.7Pa / min, melting voltage 30~39V, melting current 20~24kA, arc stabilization current 10.0~15.0A / 6~10S;

[0037] (6) The third vacuum consumable melting: The ingot that has completed the second vacuum consumable melting is subjected to the third vacuum consumable melting. The vacuum before melting is ≤1.3Pa, the vacuum during melting is ≤5Pa, and the leakage rate is

[0038] ≤0.7Pa / min, melting voltage 30~39V, melting current 23~28kA, arc stabilization current 10.0~14.0A / 6~10S, argon filling ≤5Pa during the feeding stage, maintaining vacuum 4-5Pa;

[0039] (7) Single-phase interval fire reversing upsetting and drawing: the ingot is heated at 1080-1200℃, and after being heated through, it is taken out of the furnace and forged for 1-2 fires of upsetting and drawing. Each fire has 2 upsettings and 2 drawing. The deformation mode of the last upsetting and drawing in the last fire of this stage is axial upsetting and side drawing, which changes the original axial direction of the forging billet. After forging, it is air-cooled or the hot material is returned to the furnace; the forging billet is heated through at 20-60℃ below the phase transformation point, and then 1 upsetting and 1 drawing are carried out. After forging, the hot material is returned to the furnace and heated through at 40-120℃ above the phase transformation point, and then 1 upsetting and 1 drawing are carried out. The deformation mode of the last upsetting and drawing in the last fire of this stage is side upsetting and axial drawing. After forging, the axial direction of the billet is equivalent to the axial direction of the original ingot;

[0040] (8) Two-phase separation fire reversing upsetting and drawing: After the forging billet is heated at 20-60℃ below the phase transformation point, it is subjected to one upsetting and one drawing. After forging, it is air-cooled or the hot material is returned to the furnace. The one upsetting and one drawing process is repeated 4-6 times. In this stage, the second upsetting and drawing deformation mode is axial upsetting and side drawing, which changes the original axial direction of the forging billet. The last upsetting and drawing deformation mode is side upsetting and axial drawing. After forging, the axial direction of the billet is equivalent to the axial direction of the original ingot.

[0041] (9) Two-phase zone drawing forging: The forging blank is heated at 20 to 60°C below the phase transformation point and then drawn forged. After forging, it is air-cooled or the hot material is returned to the furnace until it is drawn and rounded to the corresponding finished bar.

[0042] The present invention can produce titanium alloy ingots with low impurities (Fe≤0.008%, O≤0.075%) and high composition uniformity. The diameter of the produced ingot product is Φ580mm-Φ780mm. At the same time, the ingot can be used to produce large-size bars with a diameter of Φ300-500mm, which is suitable for industrial production.

[0043] Preferably, in step (1), all raw materials are unpacked and used on the same day; Fe in titanium sponge is ≤0.005%, Fe in aluminum beans is ≤0.02%, Fe in Al-60Ta is ≤0.04%, O in titanium sponge is ≤0.04%, and Cl in titanium sponge is ≤0.035%; C powder is dried before use, the drying time is ≥4h, and the drying temperature is 80-120°C.

[0044] Preferably, in the steps (1) and (2), the external placement time of the raw materials is controlled, and the total time from opening the barrel of all raw materials and pressing them through the electrodes to the electrodes entering the welding box is ≤25h; in the step (3), the external placement time of the electrodes is controlled after welding, and the total time from the welding electrodes being taken out of the furnace to the first smelting and loading into the furnace is ≤25h.

[0045] Preferably, in step (7), the ingot is heated at 1080-1200°C, and after being heated through, it is taken out of the furnace and subjected to 1-2 fire upsetting and drawing forging, with each upsetting or drawing deformation being 30-45%; the forging blank is heated through at 20-60°C below the phase transformation point, and then subjected to 1 upsetting and 1 drawing, with an upsetting or drawing deformation of 20-40%, asbestos sheathing is performed before forging, and after forging, the hot material is returned to the furnace and heated through at 40-120°C above the phase transformation point, and then subjected to 1 upsetting and 1 drawing, with an upsetting or drawing deformation of 10-25%, and air cooling is performed after forging, and the cycle is repeated 1-2 times at 20-60°C below the phase transformation point and 40-120°C above the phase transformation point.

[0046] Preferably, in the step (8), the forging blank is heated at 20 to 60°C below the phase transformation point and then subjected to upsetting and drawing, with the upsetting or drawing deformation amount being 20 to 40%, and asbestos sheathing before forging.

[0047] Preferably, in the step (9), the forging blank is heat-insulated at 20 to 60° C. below the phase transformation point and then subjected to drawing forging, and the drawing deformation amount per fire is 5 to 30%.

[0048] Also provided is a titanium alloy rod manufactured by the preparation method of the high-quality Ti60 titanium alloy rod.

[0049] The specific embodiments of the present invention are described in detail below.

[0050] Embodiment 1

[0051] Step 1) Raw material selection

[0052] The above raw materials were used according to 5.7Al-3.75Sn-3.4Zr-0.5Mo-0.4Si-1.1Ta-0.4Nb

[0053] -0.06C is added, all raw materials are opened and used on the same day, and the impurity element detection of relevant raw materials according to the above requirements is shown in Table 1 below. C powder needs to be dried before use, the drying time is 4h, and the drying temperature is 100℃. The longest time for all raw materials to be opened and pressed by electrodes to enter the welding box is 24.3h.

[0054] Table 1 Impurity element content of raw materials Wt%

[0055] Raw material types Fe content O content Cl content Titanium sponge 0.00500 0.040 0.032 Al bean 0.02000 0.007 / Al-60Ta 0.04000 0.034 /

[0056] Step 2) Electrode pressing

[0057] After mixing the above raw materials for 60-90s, titanium sponge is used as the base during pressing to reduce the powdery intermediate alloy from spreading during the pressing process. The powdery intermediate alloy is pressed into a density of 3.3-3.6g / cm using a hydraulic press. 3 The electrode block has a specification of Φ420mm.

[0058] Step 3) Electrode welding

[0059] In the vacuum plasma welding box, a water-cooled copper electrode head welding gun is used to perform argon filling welding on the electrode block. The welds are evenly and symmetrically distributed on the circumference, the pre-vacuum is 0.08mbar, the leakage rate is ≤0.008mbar / min, the argon flow rate is 10-27L / min, and the longest time from the welding electrode being taken out of the furnace to the first smelting and loading into the furnace is 23.5h.

[0060] Step 4) First vacuum consumable melting

[0061] The welded electrode is subjected to the first vacuum consumable melting, with the vacuum before melting ≤2Pa, the vacuum during melting ≤8Pa, the leakage rate ≤0.8Pa / min, the melting voltage 31-39V, the melting current 13-18kA, the arc stabilization current 8.0-10.0A (DC), and the specification of the ingot after one melting is Φ500mm.

[0062] Step 5) Second vacuum consumable melting

[0063] The ingot that has completed the first vacuum consumable melting is subjected to the second vacuum consumable melting, with the vacuum before melting ≤1.3Pa, the vacuum during melting ≤5Pa, the leakage rate ≤0.7Pa / min, the melting voltage 30~39V, the melting current 20~24kA, the arc stabilizing current 10.0~15.0A / 6~10S (AC), and the specification of the ingot after the second melting is Φ600mm.

[0064] Step 6) The third vacuum consumable melting

[0065] The ingot that has completed the second vacuum consumable melting is subjected to the third vacuum consumable melting, with the vacuum before melting ≤1.3Pa, the vacuum during melting ≤5Pa, the leakage rate ≤0.7Pa / min, the melting voltage 30-39V, the melting current 23-28kA, the arc stabilizing current 10.0-14.0A / 6-10S (AC), and when there are 255kg of consumable electrode left, argon is filled in to maintain the vacuum 4Pa. The specifications of the ingots after the three meltings are Φ680mm.

[0066] The Φ680mm ingot produced by the above process is longitudinally measured at the head, middle, bottom, upper and lower positions (see Figure 1 ) The chemical composition test results are shown in Table 2. The 9 o'clock position of the ingot riser end (see Figure 2The results of the chemical composition test of the Al element are shown in Table 3. The results show that the distribution of each element at each position is uniform and the fluctuation is small, and the impurity elements Fe≤0.008% and O<0.075%, which shows that the present invention can achieve the purpose of preparing a titanium alloy ingot with low impurities and high composition uniformity.

[0067] Table 2 Chemical composition detection values ​​Wt% at each position in the longitudinal direction of the ingot

[0068]

[0069] Table 3 Chemical composition of Al element at each transverse position of the ingot riser end Wt%

[0070]

[0071] Step 7) Single-phase fire separation reversing upsetting

[0072] The ingot is heated at 1150℃ (the phase change point of the ingot is 1040℃), and after being heated through, it is taken out of the furnace for the first fire upsetting and drawing forging. The deformation of each upsetting or drawing is 40%. This fire is 2 upsetting and 2 drawing. The last 1 upsetting and 1 drawing is the shaft upsetting and side drawing. After forging, it is air-cooled.

[0073] After the first forging, the billet is heated at 30℃ (1010℃) below the phase transformation point and then taken out of the furnace for the second forging. The deformation of each upsetting or drawing is 30%. This time, one upsetting and one drawing are performed. Asbestos is wrapped before forging. After forging, the hot material is returned to the furnace and heated at 100℃ (1140℃) above the phase transformation point. After the third forging, the deformation of each upsetting or drawing is 20%. This time, one upsetting and one drawing are performed. Air cooling is performed after forging.

[0074] After the third forging, the billet is heated at 40℃ (1000℃) below the phase transformation point and then taken out of the furnace for the fourth forging. The deformation of each upsetting or drawing is 30%. This time, one upsetting and one drawing are performed. Asbestos is wrapped before forging. After forging, the hot material is returned to the furnace and heated at 40℃ (1080℃) above the phase transformation point. After forging, it is taken out of the furnace for the fifth forging. The deformation of each upsetting or drawing is 20%. This time, one upsetting and one drawing are performed. Air cooling is performed after forging. One upsetting and one drawing are side upsetting and shaft drawing.

[0075] Step 8) Two-phase zone separation and reversing upsetting

[0076] After the fifth forging, the billet is heated at 20℃ below the phase transition point (1020℃) and then taken out of the furnace for the sixth forging. The deformation of each upsetting or drawing is 30%. This time, one upsetting and one drawing are performed. Asbestos is wrapped before forging and air-cooled after forging.

[0077] After the sixth forging, the billet is heated at 20℃ below the phase transition point (1020℃) and then taken out of the furnace for the seventh forging. The deformation of each upsetting or drawing is 30%. This fire is 1 upsetting and 1 drawing. Asbestos is wrapped before forging and air-cooled after forging. 1 upsetting and 1 drawing are shaft upsetting and side drawing.

[0078] After the 7th forging, the billet is heated at 30℃ (1010℃) below the phase transition point and then taken out of the furnace for the 8th forging. The deformation of each upsetting or drawing is 30%. This time, one upsetting and one drawing are performed. Asbestos is wrapped before forging and air-cooled after forging.

[0079] After the 8th forging, the billet is heated at 30℃ (1010℃) below the phase transition point and then taken out of the furnace for the 9th forging. The deformation of each upsetting or drawing is 30%. This fire is 1 upsetting and 1 drawing. Asbestos is wrapped before forging and air-cooled after forging. 1 upsetting and 1 drawing are side upsetting and shaft drawing.

[0080] Step 9) Two-phase stretch forging

[0081] After the 9th forging, the billet is heated at 30℃ (1010℃) below the phase transformation point and then taken out of the furnace for the 10th forging. The elongation deformation is 30%. This is a straight drawing and air cooling after forging.

[0082] After the 10th forging, the billet is heated at 30℃ (1010℃) below the phase transformation point and then taken out of the furnace for the 11th forging. The elongation deformation is 25%. This is straight drawing and air cooling after forging.

[0083] After the 11th forging, the billet is heated at 35℃ (1005℃) below the phase transformation point and then taken out of the furnace for the 12th forging. The elongation deformation is 15%. This is straight drawing and air cooling after forging.

[0084] After the 12th forging, the billet is heated at 35℃ (1005℃) below the phase transition point and then taken out of the furnace for the 13th forging. The elongation deformation is 8%. In this fire, the billet is straight drawn and rounded to a Φ350mm finished bar, and air-cooled after forging.

[0085] By performing transverse and longitudinal microstructure tests on the same parts of the finished rods, it can be found that the transverse and longitudinal microstructures are slightly directional, but the difference in the transverse and longitudinal directions is small, indicating that the overall microstructure uniformity of the rod is good. Ultrasonic flaw detection is performed on the circumferential surface of the rod, and the flaw detection noise level is Φ0.8-(4~14)dB.

[0086] The rods were heat treated and then tested for performance. The test results are shown below. The results show that the various properties (especially the creep property and thermal stability plasticity) are good, indicating that the present invention can produce a large-size Ti60 titanium alloy rod with high creep performance and relatively high plasticity.

[0087] Table 4 Mechanical properties test results of finished bars

[0088]

[0089] Implementation counter-example 1

[0090] Except that the third vacuum melting is not filled with argon and no reversing upsetting is performed during forging, the rest is consistent with Example 1. The transverse Al element wave at the ingot riser end is significantly larger; at the same time, the transverse microstructure directionality of the finished bar is not obvious, but the longitudinal microstructure has obvious directionality, and the difference in the directionality of the transverse and longitudinal microstructures is significantly larger, indicating that the overall structural uniformity of the bar is deteriorated; the circumferential surface of the bar is ultrasonically inspected, and the flaw detection noise level is Φ1.2-(7~15)dB, which is worse than the noise level of Example 1, which indirectly indicates that the present invention can produce a large-size Ti60 titanium alloy bar with high composition uniformity, high structural uniformity, and high flaw detection level.

[0091] Table 5 Chemical composition of Al element at each transverse position of the ingot riser end Wt%

[0092]

[0093] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing high-quality Ti60 titanium alloy bars, characterized in that: It includes the following steps: (1) Raw material selection: The raw materials are titanium sponge with a particle size of 0.83-12.7 mm, aluminum beans with a particle size of 5.0-13.0 mm, Al-60Ta with a particle size of ≤0.8 mm, Ti-80Sn with a particle size of a×b×c, zirconium sponge with a particle size of 1.0-12.0 mm, Al-60Mo with a particle size of ≤0.8 mm, 0.25~4.0mmTi-50Si, particle size ≤1.5mmAl-60Nb, particle size 200 mesh C powder, the range of a is 3.0~15.0mm, the range of b is 3.0~5.0mm, and the range of c is 0.05~0.5mm; (2) Electrode pressing: After mixing the above raw materials for 30-90 seconds, use an 8000-ton hydraulic press to press them into a density of 3.5-3.6 g / cm 3 The electrode block is pressed with titanium sponge as the base to reduce the powdered master alloy from spilling during the pressing process; (3) Electrode welding: In a vacuum plasma welding box, a water-cooled copper electrode tip welding gun is used to perform argon-filled welding on the electrode block. The weld is evenly and symmetrically distributed on the circumference. The pre-vacuum is ≤0.08 mbar, the leakage rate is ≤0.008 mbar / min, and the argon flow rate is 10 to 27 L / min. (4) The first vacuum consumable melting: The welded electrode is subjected to the first vacuum consumable melting, with the vacuum before melting ≤2Pa, the vacuum during melting ≤8Pa, the gas leakage rate ≤0.8Pa / min, the melting voltage 29-35V, the melting current 13-18kA, and the arc stabilization current 6.0-10.0A; (5) Second vacuum consumable melting: The ingot that has completed the first vacuum consumable melting is subjected to the second vacuum consumable melting, with the vacuum before melting ≤1.3Pa, the vacuum during melting ≤5Pa, the leakage rate ≤0.7Pa / min, the melting voltage 30~39V, the melting current 20~24kA, and the arc stabilization current 10.0~15.0A / 6~10S; (6) The third vacuum consumable melting: The ingot that has completed the second vacuum consumable melting is subjected to the third vacuum consumable melting, with the vacuum before melting ≤1.3Pa, the vacuum during melting ≤5Pa, the leakage rate ≤0.7Pa / min, the melting voltage 30~39V, the melting current 23~28kA, and the arc stabilization current 10.0~14.0A / 6~10S, during the feeding stage, fill with argon ≤5Pa, maintain vacuum 4-5Pa; (7) Single-phase interval fire reversing upsetting and drawing: the ingot is heated at 1080-1200℃, and after being heated through, it is taken out of the furnace and forged for 1-2 fires of upsetting and drawing. Each fire has 2 upsettings and 2 drawing. The deformation mode of the last upsetting and drawing in the last fire of this stage is axial upsetting and side drawing, which changes the original axial direction of the forging billet. After forging, it is air-cooled or the hot material is returned to the furnace; the forging billet is heated through at 20-60℃ below the phase transformation point, and then 1 upsetting and 1 drawing are carried out. After forging, the hot material is returned to the furnace and heated through at 40-120℃ above the phase transformation point, and then 1 upsetting and 1 drawing are carried out. The deformation mode of the last upsetting and drawing in the last fire of this stage is side upsetting and axial drawing. After forging, the axial direction of the billet is equivalent to the axial direction of the original ingot; (8) Two-phase separation fire reversing upsetting and drawing: After the forging blank is heated at 20-60℃ below the phase transformation point, it is subjected to one upsetting and one drawing. After forging, it is air-cooled or the hot material is returned to the furnace. The one-upsetting and one-drawing process is repeated 4-6 times. In this stage, the second upsetting and drawing deformation mode is shaft upsetting and side drawing, and the last upsetting and drawing deformation mode is side upsetting and shaft drawing. (9) Two-phase zone drawing forging: The forging blank is heated at 20 to 60°C below the phase transformation point and then drawn forged. After forging, it is air-cooled or the hot material is returned to the furnace until it is drawn and rounded to the corresponding finished bar.

2. The method for preparing high-quality Ti60 titanium alloy bars according to claim 1, characterized in that: In the step (1), all raw materials are unpacked and used on the same day; Fe in titanium sponge is ≤0.005%, Fe in aluminum beans is ≤0.02%, Fe in Al-60Ta is ≤0.04%, O in titanium sponge is ≤0.04%, and Cl in titanium sponge is ≤0.035%; C powder is dried before use, the drying time is ≥4h, and the drying temperature is 80-120°C.

3. The method for preparing high-quality Ti60 titanium alloy rod according to claim 2, characterized in that: In the steps (1) and (2), the external placement time of the raw materials is controlled, and the total time from opening the barrel of all raw materials and pressing them through the electrodes to the electrodes entering the welding box is ≤25 hours; in the step (3), the external placement time of the electrodes is controlled after welding, and the total time from the welding electrodes being taken out of the furnace to the first smelting and loading into the furnace is ≤25 hours.

4. The method for preparing high-quality Ti60 titanium alloy rod according to claim 3, characterized in that: In the step (7), the ingot is heated at 1080-1200°C, and after being heated through, it is taken out of the furnace and subjected to 1-2 fire upsetting and drawing forging, and the upsetting or drawing deformation is 30-45% each time; the forging blank is heated through at 20-60°C below the phase transformation point, and then subjected to one upsetting and one drawing, and the upsetting or drawing deformation is 20-40%, asbestos sheathing is performed before forging, and after forging, the hot material is returned to the furnace and heated through at 40-120°C above the phase transformation point, and then subjected to one upsetting and one drawing, and the upsetting or drawing deformation is 10-25%, and air cooling is performed after forging, and the cycle is repeated 1-2 times at 20-60°C below the phase transformation point and 40-120°C above the phase transformation point.

5. The method for preparing high-quality Ti60 titanium alloy rod according to claim 4, characterized in that: In the step (8), the forging blank is heated at 20 to 60°C below the phase transformation point, and then subjected to upsetting and drawing, with the upsetting or drawing deformation amount being 20 to 40%, and asbestos sheathing before forging.

6. The method for preparing high-quality Ti60 titanium alloy rod according to claim 5, characterized in that: In the step (9), the forging blank is heated at 20 to 60°C below the phase transformation point and then subjected to drawing forging, with the drawing deformation amount of 5 to 30% per fire.

7. A titanium alloy bar manufactured according to the method for preparing a high-quality Ti60 titanium alloy bar according to any one of claims 1 to 6.